Jejak seorang pemimpin : sejarah lisan Tun Dr. Mahathir Mohamad. (Petaling Jaya, Selangor : MPH Group Publishing Sdn Bhd, 2014)
An oral history of politics and government by former Prime Minister Tun Mahathir bin Mohamad in Malaysia.
Includes index.
In Malay.
Keywords: Mahathir Mohamad, -- Tun, -- 1925-; Malays; Malaysia -- Politics and government